Neutrophil elastase activates the release of extracellular traps from COPD blood monocyte‐derived macrophages - Shuo Zheng; Apparao B. Kummarapurugu; Gamze B. Bulut; Aamer Syed; Le Kang; Judith A. Voynow (Wiley, 2023)
Abstract Neutrophil elastase (NE), a major inflammatory mediator in chronic obstructive pulmonary disease (COPD) airways, impairs macrophage function, contributing to persistence of airway inflammation. We hypothesized that NE activates a novel mechanism of macrophage‐induced inflammation: release of macrophage extracellular traps (METs). The METs are composed of extracellular DNA decorated with granule proteinases and oxidants and may trigger persistent airway inflammation in COPD. To test the hypothesis, human blood monocytes were isolated from whole blood of subjects with COPD recruited following informed written consent. Patient demographics and clinical data were collected. Cells were cultured in media with GM‐CSF to differentiate into blood monocyte derived macrophages (BMDMs). The BMDMs were treated with FITC‐NE and unlabeled NE to determine intracellular localization by confocal microscopy and intracellular proteinase activity by DQ‐Elastin assay. After NE exposure, released extracellular traps were quantified by abundance of extracellular DNA in conditioned media using the Pico Green assay. BMDM cell lysates were analyzed by Western analysis for proteolytic degradation of histone H3 or H4 or upregulation of peptidyl arginine deiminase (PAD) 2 and 4, two potential mechanisms to mediate extracellular trap DNA release. We observed that NE was taken up by COPD BMDM, localized to the cytosol and nucleus, and retained proteinase activity in the cell. NE induced MET release at doses as low as 50 nM. NE treatment caused histone H3 clipping but no effect on histone H4 nor PAD 2 or 4 abundance or activity. In summary, NE activated COPD MET release by clipping histone H3, a prerequisite for chromatin decondensation.